Analysis of qCON and qNOX Anesthesia Indices and EEG Spectral Energy during Natural Sleep Stages - Joana Cañellas; Anaïs Espinoso; Juan Felipe Ortega; Umberto Melia; Carmen González; Erik Weber Jensen (Advances in Science, Technology and Engineering Systems Journal, 2021)
The objective of this research is to study the behaviour of the anaesthesia monitor Conox during natural sleep to open the gate for this devices to assess subjects during this stage. The values of qCON and qNOX indices and EEG frequency bands are analysed during night sleep of 10 volunteers when they lose consciousness, in order to determine if they can be used for monitoring sleep. The possibility of using these indexes to differentiate between NREM/REM cycles of night sleep is studied. A reduction in the hypnotic index was observed while the nociception index stayed significantly higher. Statistical differences where found for qCON between sleep cycles, allowing this index to detect REM intervals and possibly opening the gate to use depth of anaesthesia devices to monitor sleep.
Keywords: Sleep; consciousness; Nociception; Anaesthesia; Monitor; REM; NREM